Artificial Intelligence (AI) in Islamic Finance: A PRISMA-Guided Systematic Review on Sharia Compliance - Manneh, Kekoto; Susilowati, Endah; Sundari, Siti (EQUILIBRIUM, 2025)
This paper seeks to explore the role of AI in the Islamic finance context, in terms of its opportunities, challenges, and its compliance with Sharia principles. The adaptation of AI has transformed traditional finance. However, its integration into Islamic finance is still fragmented, which raises doubts about its alignment with the core principles of Sharia ethics and governance. In order to address this existing gap, the study adopts a PRISMA-guided systematic review, synthesizing and analyzing 26 peer-reviewed publications published between 2020 and 2025. Findings of this study reveal that AI adaptation has several opportunities which enhance efficiency, transparency, financial inclusion, and Sharia auditing; all aligning with the core of Maqasid al-Sharia (higher objectives of Shari’ah rules). Despite these opportunities, several challenges such as high implementation cost, skills gap, cybersecurity risks, and algorithmic bias, affect the implementation of AI in Islamic finance. The major issue about these difficulties is the conformity of Sharia with regulatory gaps and the expanding responsibilities of Sharia boards, necessitating immediate attention. The study has limitations as it relies on secondary data obtained from Scopus-Indexed and Google Scholar databases. It has been recommended to future researchers to adopt empirical studies and cross-disciplinary collaboration regarding AI’s integration into Islamic finance to ensure that it maintains both innovative and compliant.